1969
DOI: 10.1002/hlca.19690520404
|View full text |Cite
|
Sign up to set email alerts
|

Sur la composition de l'arôme de tomate

Abstract: (5 I11 69) Sumnzary. A gas-chromatographic investigation of tomato aroma has revealed 46 components of which 32 are new. The isolation and identification of 2-isobutyl-thiazole, substance for the first time found in a natural aroma, are given in detail. Le tableau Cnunikre tous les composCs que nous avons trouv6s au cours de notre recherche ; ceux qui sont nouveaux sont en italique. Parmi ceux-ci, seul l'isobutyl-2-thiazole n'a pas encore CtC, i notre connaissance, identifiC dans un ar6me naturel; nous dCcrivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Dunstan and Henry speculated about the presence of ortho-acetophenone and possible derivatives which may contribute to the faecal odour of the fresh wood. According to literature ortho-acetophenone contributes to the odour of various plants, such as cacao (Marion et al, 1967;Flament et al, 1967), coffee and tomatoes (Viani et al, 1969).…”
Section: Resultsmentioning
confidence: 98%
“…Dunstan and Henry speculated about the presence of ortho-acetophenone and possible derivatives which may contribute to the faecal odour of the fresh wood. According to literature ortho-acetophenone contributes to the odour of various plants, such as cacao (Marion et al, 1967;Flament et al, 1967), coffee and tomatoes (Viani et al, 1969).…”
Section: Resultsmentioning
confidence: 98%
“…2-IsobutyIthiazoIe was synthesized (Viani et al, 1969) in low but adequate yield by the addition of 2-chloroacetaldehyde to the crude product from the reaction of valeramide with phosphorus pentasulfide.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been demonstrated that benzothiazole can arise as a contaminant from rubber tubing used in distillation techniques (Ferretti and Flanagan, 1973). Only a limited amount of information on the odor qualities of thiazole derivatives is available; these range from the objectionable pyridine-like odor of thiazole itself (Webster, 1964) and quinoline-like benzothiazole (Merck, 1968) through the strong tomato leaf odor of 2-isobutylthiazole (Viani et al, 1969) to the pleasant bread-crust flavor of 2-acetyl-2-thiazoline (Tonsbeek etal, 1971).…”
Section: Comparative Study Of Flavor Properties Of Thiazole Derivativesmentioning
confidence: 99%